Livros didáticos de Língua Portuguesa: refrações sobre o escopo político-ideológico e o ensino público no Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
This study falls within the scope of Applied Linguistics and its main objective was to analyze a collection of Portuguese language books adopted in high school in public schools in the city of Manaus, as a result of Public Policies. It is based, therefore, on the theoretical-epistemological and methodological assumptions of the Bakhtin Circle (BAKHTIN, 2010; VOLÓCHINOV, 2017), as well as on the Dialogical Analysis of Discourse (BRAIT, 2006). The specific objectives consisted of (1) investigating the factors that cross the didactic material at the national level, considering its ideological, political and social constitution; (2) analyzing the textual materiality of the didactic material, which make up the corpus of the research, based on official documents that guide the teaching of the Portuguese language aimed at secondary education at the national and regional level; (3) apprehend the aspects of the discursive constitution that sustain the didactic material analyzed as basic instruments of teaching-learning, construction of knowledge and formation of social subjects. As a subsidy of the investigation, the official documents that guide Education at the national and regional level were observed - Parâmetros Curriculares Nacionais Ensino Médio (BRASIL, 1999); Proposta Curricular de Língua Portuguesa Para o Ensino Médio (AMAZONAS, 2012); Base Nacional Comum Curricular (BRASIL, 2017) – as well as Plano Nacional do Livro Didático (BRASIL, 2018; 2020). In addition to the structural production conditions that affect the analyzed collection, we demarcate the presence of the ideological, political, economic, didactic, social and historical function in the educational perspective and its reflection and refraction in the materialized teaching practice. We thus apprehend that the analyzed books and, by extension, all didactic material resulting from educational public policies, constitute a valuable historical cultural and documental archive about the educational sphere and that contributed and actively contributes to the formation and promotion of teaching and learning at the national level.
Portuguese Language textbooks: refractions about the political-ideological scope and teaching public in Amazonas
Keywords: Livros didáticos; Língua portuguesa - Estudo e ensino (Ensino médio); LINGUISTICA, LETRAS E ARTES: LINGUISTICA: TEORIA E ANALISE LINGUISTICA; LINGUISTICA, LETRAS E ARTES: LINGUISTICA: LINGUISTICA APLICADA; Livro Didático; Ideologia; Políticas Públicas; Educação Básica